Attitudes towards immigration and refugees in Ireland: Understanding recent trends and drivers - Laurence, James; McGinnity, Frances; Murphy, Keire (ESRI, 2024)
This report draws on several high quality, nationally representative surveys, along with a unique survey experiment, to conduct a comprehensive analysis of where attitudes towards immigration in Ireland currently stand today, how they have changed in recent years, how they differ for different types of migrants. What factors in people’s lives are associated with their attitudes towards migrants, immigration and the acceptability of protesting international protection arrivals?